Satisfaction and perception of house owner towards QLASSIC assessment / Nurita Saperi - Saperi, Nurita (Faculty of Architecture, Planning and Surveying, 2013)
A shelter or generally known as a house or residential are the basic necessities of everyone’s life. Most people did, some are in the process of purchasing, while others are planning to purchase their own houses and all of them are expect the house purchased in good condition. But unfortunately, the quality issues always hear from complaints by the house buyer when they enter their new house. This problem leads to unsatisfactory of house owner on the house purchased. The objectives of this research are to identify the tools for quality assessment system used in construction industry, to review house owner’s awareness on QLASSIC towards construction industry, to discover home owner’s satisfaction on quality aspects and to identify house owner’s perception on implementation QLASSIC system. The questionnaire is being used which are contributed to the house owners in Klang Valley areas in order to identify those objective. Based on the finding, one of the tools to scrutinize construction quality is by QLASSIC that had introduced by CIDB as a construction quality assessment. It is similar with CONQUAS, which had been introduced and practiced by BCA Singapore, and PASS. Most of house owners have low awareness on QLASSIC assessment.However, average index for house owner satisfaction is “high” shows that overall house owner is satisfy with their house. As a perception on QLASSIC, it can be concluded that QLASSIC is actually beneficial to the house owners and they want QLASSIC assessment to be mandatory to get the best quality of the house.